Online Buying Behavior During Covid – 19 Pandemic: A Descriptive Analysis Study - Retno Dyah Kusumastuti; Siti Maryam; Ana Kuswanti; Airlangga Surya Kusuma (International Journal of Business Studies, 2022)
Since its first inception during the 1990s, electronic commerce (e-commerce) has revolutionized costumers buying behavior and caused the costumers to shift from traditional brick-and-mortar stores into online stores. In Indonesia, e-commerce market has enjoyed rapid growth around 60 to 70 percent annually since 2014. On the other hand, the Covid – 19 pandemic is still ravaging Indonesia. This pandemic caused concerns among costumers in Indonesia, due to the higher risk of Covid – 19 transmission during buying activities in traditional brick-and-mortar stores. Thus, buying from online stores became more convenient and safer option for customers. The purpose of this research is to investigate about customers online buying behavior during the Covid – 19 pandemic. This research utilized quantitative and descriptive approach, with 200 respondents participated during the survey. The findings of this research are that the majority of respondents might have shifted from offline buying to online buying, albeit not significantly. On the other hand, the majority of respondents chose to not spend a large amount of money for online buying activities. The majority of respondents also bought fashion and beauty care products from online platforms, and because of Covid – 19 pandemic, a large number of respondents also bought healhcare equipment from online platforms. The implication of this research is that it would be better if traditional brick-and-mortar retailers start transitioning to e-commerce, since customers might permanently shift to online buying, even after the Covid – 19 pandemic has been contained.